2011
DOI: 10.1088/0004-637x/730/2/70
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Formation in Failing Core-Collapse Supernovae

Abstract: We investigate several aspects of black hole formation in failing core-collapse supernovae using 1D general-relativistic hydrodynamic simulations. We use the open-source code GR1D and incorporate into it nucleon-nucleon Bremsstrahlung, a crucial neutrino pair-production channel. We focus on how various thermal effects can influence the postbounce supernova evolution towards black hole formation. By performing simulations with and without nucleon-nucleon Bremsstrahlung, we investigate the sensitivity of black h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
653
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 724 publications
(684 citation statements)
references
References 94 publications
27
653
3
1
Order By: Relevance
“…By replacing the proto-neutron star (PNS) interior with an inner boundary condition, they followed an unprecedentedly long-term evolution over hours to days after bounce in spherical symmetry. Their results also lent support to the finding by O'Connor & Ott (2011) that the compactness parameter is a good measure to diagnose the progenitor-explosion and the progenitor-remnant correlation (see also Pejcha & Thompson 2014;Perego et al 2015).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…By replacing the proto-neutron star (PNS) interior with an inner boundary condition, they followed an unprecedentedly long-term evolution over hours to days after bounce in spherical symmetry. Their results also lent support to the finding by O'Connor & Ott (2011) that the compactness parameter is a good measure to diagnose the progenitor-explosion and the progenitor-remnant correlation (see also Pejcha & Thompson 2014;Perego et al 2015).…”
Section: Introductionsupporting
confidence: 70%
“…Here it should be noted that the above threshold is for a cold NS, whereas the PNS soon after bounce is still hot. At this phase, the contribution of thermal pressure to the maximum mass cannot be neglected, so that the maximum mass of the hot PNS is bigger than that of the cold NS (O'Connor & Ott 2011;Hempel et al 2012). Based on a systematic 1D GR simulation with approximate neutrino transport, O'Connor & Ott (2011) showed that the maximum gravitational mass of the hot PNSs, which is bigger for models with high compactness, ranges from 2.1M ⊙ (ξ 2.5,cb = 0.20) 2 to 2.5 M ⊙ (1.15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter prescription is under the assumption that the BH formation is controlled by the compactness of the stellar core at the time of collapse: low compactness stars are more likely to explode as SNe and produce NSs, while high-compactness stars are more likely to evolve to failed SNe that produce BHs (O'Connor & Ott 2011). In this case we assume MBH = MHe or MCO, where MHe is the He core masses prior to core collapse (e.g., Smith et al 2011;Smith & Arnett 2014;Shiode & Quataert 2014;Sukhbold & Woosley 2014;Clausen et al 2015;Kochanek 2014Kochanek , 2015.…”
Section: Remnant Massmentioning
confidence: 99%
“…The delayed neutrino-heating model for CCSNe posits that a small fraction of the neutrinos emitted from near the protoneutron star are absorbed near the stalled shock, thereby depositing enough energy to reinvigorate the shock's outward progress. This shock revival must occur within a few hundreds of milliseconds to ∼1-2 s of core bounce to avoid black hole formation or a top-heavy neutron star mass distribution (O'Connor & Ott 2011). Since the neutrino mechanism strongly depends on how efficiently energy is transported by neutrinos from near the protoneutron star to the region just behind the shock and on how this energy deposition affects the hydrodynamic evolution near the shock, an accurate treatment of hydrodynamics and non-equilibrium neutrino transport is a key requirement for simulating CCSNe.…”
Section: Introductionmentioning
confidence: 99%